2022
DOI: 10.1002/joc.7560
|View full text |Cite
|
Sign up to set email alerts
|

Early summer surface air temperature variability over Pakistan and the role of El Niño–Southern Oscillation teleconnections

Abstract: Early summer (May–June) is the season where the surface air temperature (SAT) variability is largest and may result in extreme temperature conditions over Pakistan. Therefore, we analysed the early summer interannual SAT variability over Pakistan for the period 1981–2018 using observational dataset and model simulations. We noted that upper‐level anticyclonic circulation anomalies over Pakistan, which are associated with upper to the middle tropospheric descending motion, favour clear skies with an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 70 publications
4
9
0
Order By: Relevance
“…3b), similar to observations (Fig. 3a), and this is consistent with earlier findings (Rashid et al 2022). A significant SST anomaly signal also appears over the western Indian Ocean and tropical Atlantic region but in this study, we focus on ENSO forced predictability for the regional temperature.…”
Section: Seasonal Forecast Systemsupporting
confidence: 92%
See 3 more Smart Citations
“…3b), similar to observations (Fig. 3a), and this is consistent with earlier findings (Rashid et al 2022). A significant SST anomaly signal also appears over the western Indian Ocean and tropical Atlantic region but in this study, we focus on ENSO forced predictability for the regional temperature.…”
Section: Seasonal Forecast Systemsupporting
confidence: 92%
“…Moreover, ERA5 SAT reasonably well compares with the observational SAT from CRU (Correlation Coefficient; CC=0.94) and CPC (CC=0.94). This is consistent with earlier findings where it was shown that ERA5 reanalysis performs well compared to the other reanalysis over the region (Arshad et al 2021;Rashid et al 2022). We adopted European Centre for Medium-Range Weather Forecasts (ECWMF) fifth generation prediction system (ECMWF-SEAS5) reforecast dataset (Johnson et al 2019) to analyse the early summer season (May-June; MJ) SAT prediction skill over WSA using the April initial condition (Lead-1 season).…”
Section: Datasets and Methodologysupporting
confidence: 86%
See 2 more Smart Citations
“…An additional mechanism for the south-eastward propagation was attributed to the upper-tropospheric Rossby wave forcing (Zhao et al 2017). Some studies have also reported modes of interannual variability of temperature over Pakistan (Rashid et al 2022). The interannual variability of surface air temperature in Pakistan during early summer is associated with upper-level divergence and associated sinking motion in the atmosphere over South Asia which are modulated by the strengthening of Hadley and Walker circulation.…”
Section: Introductionmentioning
confidence: 99%